Post-operative Outcome during Off-Pump Coronary Artery Bypass Surgery – A Comparison between Combined High Thoracic Epidural Anaesthesia with General Anaesthesia and General Anaesthesia Alone (Cardiovascular Journal, 2022)
Background: In the postoperative period inadequate analgesia may increase morbidity by causing adverse haemodynamic, metabolic, immunologic and haemostatic attentions and prolong mechanical ventilation with more ICU stay. This study has been undertaken to compare postoperative outcome in off-pump coronary artery bypass surgery (OPCAB) between high thoracic epidural anaesthesia (HTEA) as an adjunct to general anaesthesia (GA) vs. GA alone.Methods : This prospective, randomized case control comparative study was carried out in sixty patients without having left main coronary artery disease, left ventricular ejection fraction